Civil society and the governance of water services: German political parties’ reactions to Right2Water - Tosun, Jale; Triebskorn, Rita (Water, 2020)
The European Citizens' Initiative (ECI) Right2Water asked for guaranteed water quality and quantity all over Europe, and demanded that water services remain in the hands of public entities. Support for Right2Water was particularly pronounced in Germany. The German organisers managed to collect 16 times more signatures than the minimum necessary to be counted towards the quorum. How have the German political parties reacted to the overwhelming public support for Right2Water? To answer this question, we examined the election manifestos of the main political parties, published for the federal elections in 2005, 2009, 2013, and 2017, and the elections to the European Parliament in 2004, 2009, 2014, and 2019. We concentrated on one specific goal of Right2Water, which refers to preventing the liberalisation of water services in the European Union. We expected the attention to and positioning of the liberalisation of water services to vary across the individual German parties. Since Right2Water was organised by public service trade unions and pursues an anti-liberalisation agenda, we expected left-wing parties to have laid a greater emphasis on this issue than right-wing parties, and for them to have adopted positions that aligned with the goals of the ECI. Our empirical findings show that a left-right division exists among the parties concerning the attention they paid to this issue as well as how they positioned themselves.